2016
DOI: 10.1016/j.neuroscience.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortical plasticity in extrinsic hand muscles is determined by the resting thresholds of overlapping representations

Abstract: Knowledge of the properties that govern the effectiveness of transcranial magnetic stimulation (TMS) interventions is critical to clinical application. Extrapolation to clinical populations has been limited by high inter-subject variability and a focus on intrinsic muscles of the hand in healthy populations. Therefore, the current study assessed variability of continuous theta burst stimulation (cTBS), a patterned TMS protocol, across an agonist–antagonist pair of extrinsic muscles of the hand. Secondarily, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Furthermore, we did not assess the cortical excitability of the soleus muscle in the current work. Previous studies reported that the overlapping cortical representations with proximal antagonist muscle affect each TBS (Mirdamadi et al, 2015(Mirdamadi et al, , 2016. Similarly, TBS to the motor cortex area of soleus muscleareas that overlaps with TA muscle may affect our results.…”
Section: Limitationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, we did not assess the cortical excitability of the soleus muscle in the current work. Previous studies reported that the overlapping cortical representations with proximal antagonist muscle affect each TBS (Mirdamadi et al, 2015(Mirdamadi et al, , 2016. Similarly, TBS to the motor cortex area of soleus muscleareas that overlaps with TA muscle may affect our results.…”
Section: Limitationsmentioning
confidence: 61%
“…Considering both lower-limb motor cortices are proximally located, it is difficult to apply TBS to the motor cortex of one hemisphere without stimulating the other, especially at higher stimulus intensity (Huang et al, 2018;Lin et al, 2019). Additionally, the interaction between synergistic and antagonist cortical representations of arm muscles affects the plasticity induced by TBS (Mirdamadi et al, 2015(Mirdamadi et al, , 2016. Therefore, the inducibility of LTP-like or LTD-like synaptic plasticity is different in different motor cortical representations.…”
Section: Interindividual Variability In Corticospinal Excitability Chmentioning
confidence: 99%
“…The TMS measures most commonly used in the analysis of motor data are resting motor threshold (MT; the minimal TMS intensity required to evoke an MEP), latency (the time from triggering the pulse to the start of the MEP), amplitude (baseline to peak or peak to peak value) and area (measured as root mean squared, or as the area under the line of the rectified signal) [57]. MT is the lowest stimulus intensity of TMS that elicits a recordable MEP in the target muscle [58].…”
Section: Tms Measures and Motor Thresholdmentioning
confidence: 99%
“…Currently, common neuromodulation therapies for CPSP in clinical practice include repetitive transcranial stimulation, motor cortex electrical stimulation, and deep brain stimulation (Mirdamadi et al 2016;Liu et al 2020). Our research explored optogenetics as an alternative neuromodulation approach.…”
Section: Introductionmentioning
confidence: 99%